DEVELOPMENT AND IMPLEMENTATION OF SMART STREET LIGHT SYSTEM BASED ON LORA AND RADAR TECHNOLOGY - Rohit. D. Danake1,Rajkumar Gavde2; Prof. B. Sampath Kumar (International Journal of Innovations in Engineering Research and Technology, 2022)
This paper concerned with the development and implementation of Smart Street light control system based using Led lamp and Lora Wireless communication with Radar technology currently, a traditional street lights are automatically turn on or off based on timer or day/night sensor. Recently, the conventional light sources are replaced by Led, which have so many advantages such as: energy savings, long lifetime, high reliability, pure light color, fast response, and friendliness to the environment. Furthermore, the intensity of the LED can be controlled easily. In this paper, the smart lighting system is designed to control and monitor devices via wireless transmission frequencies below 1 GHz.